Does Keynesian theory explain Indian government bond yields? - Tanweer Akram; Anupam Das (Levy Economics Institute of Bard College, 2015)
John Maynard Keynes held that the central bank's actions determine long-term interest rates through short-term interest rates and various monetary policy measures. His conjectures about the determinants of long-term interest rates were made in the context of advanced capitalist economies, and were based on his views on ontological uncertainty and the formation of investors' expectations. Are these conjectures valid in emerging markets, such as India? This paper empirically investigates the determinants of changes in Indian government bonds' nominal yields. Changes in short-term interest rates, after controlling for other crucial variables such as changes in the rates of inflation and economic activity, take a lead role in driving changes in the nominal yields of Indian government bonds. This vindicates Keynes's theories, and suggests that his views on long-term interest rates are also applicable to emerging markets. Higher fiscal deficits do not appear to raise government bond yields in India. It is further argued that Keynes's conjectures about investors' outlooks, views, and expectations are fairly robust in a world of ontological uncertainty.
Keywords: E43; E50; E60; O16; 330; Government Bond Yields; India; Emerging Markets